2015
DOI: 10.1242/jeb.125260
|View full text |Cite
|
Sign up to set email alerts
|

Aestivation induces changes in transcription and translation of coagulation factor II and fibrinogen gamma chain in the liver of the African lungfish,Protopterus annectens

Abstract: This study aimed to sequence and characterize two pro-coagulant genes, coagulation factor II ( f2) and fibrinogen gamma chain ( fgg), from the liver of the African lungfish Protopterus annectens, and to determine their hepatic mRNA expression levels during three phases of aestivation. The protein abundance of F2 and Fgg in the liver and plasma was determined by immunoblotting. The results indicated that F2 and Fgg of P. annectens were phylogenetically closer to those of amphibians than those of teleosts. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 77 publications
3
7
0
Order By: Relevance
“…Indeed, our dendrogramic analyses indicated that Aqp1 and Aqp3 of P. annectens were grouped closer to tetrapods than to teleost fishes, which corroborate previous reports on the evolution of Aqp/AQP (Finn et al, 2014; Finn and Cerdà, 2015). Furthermore, our results are in agreement with previous reports on genes/proteins of P. annectens that bear close relationship with those of tetrapods (argininosuccinate lyase, Chng et al, 2014; gulonolactone oxidase, Ching et al, 2014; Na + /K + -ATPase α-subunit isoforms, Hiong et al, 2014; betaine-homocysteine S -methyltransferase 1, Ong et al, 2015; coagulation factor II and fibrinogen gamma chain, Hiong et al, 2015). …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, our dendrogramic analyses indicated that Aqp1 and Aqp3 of P. annectens were grouped closer to tetrapods than to teleost fishes, which corroborate previous reports on the evolution of Aqp/AQP (Finn et al, 2014; Finn and Cerdà, 2015). Furthermore, our results are in agreement with previous reports on genes/proteins of P. annectens that bear close relationship with those of tetrapods (argininosuccinate lyase, Chng et al, 2014; gulonolactone oxidase, Ching et al, 2014; Na + /K + -ATPase α-subunit isoforms, Hiong et al, 2014; betaine-homocysteine S -methyltransferase 1, Ong et al, 2015; coagulation factor II and fibrinogen gamma chain, Hiong et al, 2015). …”
Section: Discussionsupporting
confidence: 93%
“…Difficulties were encountered in finding a reference protein, the expression of which would be unaffected throughout the three phases of aestivation. Hence, results were expressed as arbitrary densitometric unit per μg protein, i.e., with reference to the total protein abundance, as reported elsewhere for several other proteins from P. annectens during aestivation (Ching et al, 2014; Hiong et al, 2014, 2015; Ong et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Indeed, our dendrogramic analysis indicated that Ut-a2a and Ut-a2b are grouped closer to tetrapods. This result is in agreement with the dendrogramic grouping of some proteins of P. annectens , which include Asl (Chng et al, 2014 ), Na + /K + -ATPase α-subunit isoforms (Hiong et al, 2014 ), Gulonolactone oxidase (Ching et al, 2014 ), Coagulation factor II (F2), Fibrinogen gamma chain (Hiong et al, 2015 ), Betaine-homocysteine S -methyltransferase 1 (Bhmt1; Ong et al, 2015 ), and Aquaporin 1 and 3 (Chng et al, 2016 ).…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, the mRNA expression levels of cps III (Loong et al, 2012 ), ass, asl (Chng et al, 2014 ), and bhmt1 (Ong et al, 2015 ) in the liver, and that of asl in the brain (Chng et al, 2014 ), increased significantly in P. annectens during the maintenance phase of aestivation. In addition, increases in protein abundance during the maintenance phase have been reported for Bhmt1 in the liver and muscle (Ong et al, 2015 ), F2 in the liver (Hiong et al, 2015 ), hypoxia inducible factor 1α in the gills (Garofalo et al, 2015 ), and activated eNOS/Akt and heat shock protein 90 in the lung (Garofalo et al, 2015 ) of P. annectens . Taken together, these results indicate that the supposition of expression and syntheses of all genes/proteins being suppressed in every organ in an African lungfish during the maintenance phase of aestivation may not be valid (Ip and Chew, 2010a ; Chew et al, 2015 ).…”
Section: Discussionmentioning
confidence: 96%
“…annectens , our results are in agreement with the notion that lungfish is the intermediary form between fish and tetrapods. Since lungfishes are the closest living sister group of land vertebrates, they would logically possess some genes/proteins that are closer to those of other fishes (Cps III, [ 11 ]; Ass, [ 12 ]) and others that have greater similarity to those of tetrapods (Asl, [ 12 ]; L-gulono-γ-lactone oxidase, [ 30 ]; Na + /K + -ATPase α-subunit isoforms, [ 31 ]; Coagulation factor II and Fibrinogen gamma chain [ 32 ]; Betaine-homocysteine S -methyltransferase 1, [ 33 ]; Myostatin [ 34 ]; Aquaporin 1 and 3 [ 24 ]; Urea transporter isoforms [ 29 ]).…”
Section: Discussionmentioning
confidence: 99%